Green Logístics:conceptualization and directions for practice - Santos, Jaqueline da Silva; Bortolon, Karen Munique; Chiroli, Daiane Maria de Genaro; Oiko, Olívia Toshie (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Environmental sustainability of operations is an increasing concern and there are many paths for addressing this matter. On Logistics, Green Logistic or Ecologistic is still recent and lacks ripening to handle with its environmental impacts. Its conceptual body and ways of application are not clear yet. In addition, there is often a misconception with other terms, like Reverse Logistic. This paper aims make Green Logistics concepts clear, and driving to its practice. As research method, Systematic Review of literature and Bibliometrics were conducted. Beyond conceptualization, this paper brings a brief historic of the theme, identifies technologies and strategies for application and report case studies.